Travelers along the way : a Robin Hood remix - Safi, Aminah Mae (Remixed classics., 2022)
In this reimagination of the legend of Robin Hood, Rahma al-Hud and her older sister Zeena travel to Jerusalem for a final mission, and on their way they assemble a ragtag band of misfits and get swept up Holy Land politics.